Neighbouring Interaction : A Comparative Study Of A Lower Income And Higher Income Residential Areas In Kulim - Ooi, Phaik Siew (Pusat Pengajian Ilmu Kemanusiaan, 1982)
The class factor, either measured by the level of income, education or occupation is an important influence on the individual's behaviour. One of this is his relationship with neighbours. Theclass factor is said to determine the extent and scope of neighbourliness to the extent that in certain neighbourhoods, there was virtually no contact among neighbours. This thesis was an attempt to see how status differentiation influenced neighbouring interaction.